A Case of Intraorbital Hemangioma Diagnosed with Tc 99m Labeled Erythrocyte Scintigraphy and Magnetic Resonance Imaging - Bala, Tansel Ansal; Koc, Zehra Pinar; Turgut, Burak; Aydin, Ayse Murat; Demirel, Bedriye Busra (Galenos Yayincilik, 2011)
We present a 20 year-old male patient who had prominent positional proptosis of the right eye and admitted to the hospital for tonsillectomy operation. After conventional ophthalmological examination, magnetic resonance imaging (MRI) and Tc 99m labeled erythrocyte scintigraphy were performed to confirm the diagnosis. Although it is rare to perform scintigraphy for this pathology, the visualization of intraorbital hemangioma was very obvious and we would like to present the visualization of the intraorbital hemangioma both with scintigraphy and MRI.
Keywords: Hemangioma; Technetium Tc 99m pyrophosphate; orbital neoplasms; radionuclide imaging; magnetic resonance imaging